Comparison of additives amendment for mitigation of greenhouse gases and ammonia emission during sewage sludge co-composting based on correlation analysis. (November 2017) - Wang, Meijing; Awasthi, Mukesh Kumar; Wang, Quan; Chen, Hongyu; Ren, Xiuna; Zhao, Junchao; Li, Ronghua; Zhang, Zengqiang
Graphical abstract: Highlights: Zeolite, Ca-bentonite and medical stone addition for co-composting were studied. 10% zeolite addition showed most efficient effect on composting. 10% zeolite amendment showed significantly low nitrogen loss and GHGs emission. The data provide valuable information about correlation of analyzed parameters. The co-composting of sewage sludge with Z, Ca-B and MS are feasible. Abstract: In this study, the pilot scale co-composting of sewage sludge (SS) + wheat straw amended with 10% (dry weight ratio of basis) of three different additives (zeolite, Ca-bentonite and medical stone) was conducted for 56 days to evaluate the greenhouse gases (GHGs) and nitrogen conservation efficacy and its correlation with analyzed physicochemical, gaseous and biological parameters. The results indicated that all of three additives could adequately buffer pH, considerably increase temperature, and enhance organic matter degradation as well as reduce ammonia and GHGs emission. Particularly, zeolite amended treatment showed the maximum reduction of CH4 emission by 88.45% and less amount of nitrogen loss by 28.80%, meanwhile reduced the maturity period by 2 weeks. In addition, the redundancy analysis was confirmed most significant relationship between biological, GHGs, bacterial community and nutrients concentration in 10% zeolite applied treatment than other treatments. The result suggested 10% zeolite could be a suitable additive to improve the quality of sewage sludge composting.